Hysteroscopic findings in women with recurrent IVF failures and the effect of correction of hysteroscopic findings on subsequent pregnancy rates - ÖZCAN, PINAR; Cenksoy, PINAR; Ficicioglu, Cem; Yildirim, Gazi; Yesiladali, Mert (My University, 2013)
Our aim is to evaluate the incidence of unrecognized uterine abnormalities in cases with recurrent IVF failure by screening office hysteroscopy (OH), and impacts of treatment of hysteroscopic findings on the success rate of IVF.